Pelatihan Pemanfaatan Limbah Organik Menjadi Eco-Enzyme Bagi Masyarakat Kuala Langsa - Makhroji Makhroji; Siska Rita Mahyuny; Nursamsu Nursamsu; Nur Azizah Lubis (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Eco-enzyme is a natural liquid made from waste in the form of fruit peels. The manufacturing process is very easy, it only requires water, brown sugar, cane sugar and molasses as well as fruit peels that have become waste for the community. The purpose of this service activity is to provide training in processing waste into products that can be used for the community. The method of service activities is in the form of a demonstration training method. The training participants consisted of 20 people who joined the group of Mrs. PKK Gampong Kuala Langsa, West Langsa District, Langsa City. The results of this activity at the survey stage carried out by the service team obtained permission from Mr. Geuchik to carry out service activities in Kuala Langsa Village. The socialization stage is to determine the schedule of activities and the number of participants who are given the training. The implementation phase of the activity is that the team conducts training to make eco-enzyme products for PKK. The evaluation phase of the team monitors the extent to which the product has been produced from the eco-enzyme manufacturing process. The conclusion of the service activities from distributing community satisfaction questionnaires, especially mothers who joined the PKK group were stated to be satisfied with a score of 41%, so this activity had a positive and useful impact.